2014
DOI: 10.4028/www.scientific.net/kem.600.667
|View full text |Cite
|
Sign up to set email alerts
|

Particleboards with Agricultural Wastes: Sugar Cane Bagasse and Reforestation Wood

Abstract: In this paper, it was consider the study of the use of sugarcane bagasse and wood particles, residues from the agricultural and the furniture industry, in order to add value to such materials. To add value to these materials it will be utilized in the manufacturing of hybrid panels consisting of wood particles and sugarcane bagasse in certain proportions (20%, 40% and 60%). For the production it was used the bi-component polyurethane resin based on castor oil. Analysis of the products was established based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Only a little is used for animal feed or fertilizer. While some previous studies suggested that some residues from the agricultural product could be used to form composites [2][3][4][5][6]. Rice straw contains about 40% of cellulose [7], which can be used to create a composite.…”
Section: Introductionmentioning
confidence: 99%
“…Only a little is used for animal feed or fertilizer. While some previous studies suggested that some residues from the agricultural product could be used to form composites [2][3][4][5][6]. Rice straw contains about 40% of cellulose [7], which can be used to create a composite.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these materials include sugarcane bagasse, a residue from sugarcane processing; shavings of Pinus sp., waste from the furniture industry; and polyurethane bi-component resin based on castor oil, a bender that does not emit formaldehyde during its production (CASTRO JUNIOR et al 2014).…”
Section: Introductionmentioning
confidence: 99%